Profile of Anti-Helicobacter pylori IgG Antibody Test Results in Patients with Chronic Gastritis at the Baregbeg Community Health Center - Silma Yuniar; Atun Farihatun; Euis Tia Istianah; Rahayu Nirmatul Mutmainah (Laboratory Journal of Infectious Diseases, 2026)
Gastritis is an inflammation of the gastric mucosa that may be caused by various factors, including irregular dietary habits, nonsteroidal anti-inflammatory drug (NSAID) use, psychological stress, alcohol consumption, and Helicobacter pylori infection, which is recognized as a major cause of chronic gastritis. In primary healthcare settings, identification of the underlying etiology of gastritis is often limited by the availability of diagnostic laboratory facilities. Therefore, serological detection of anti-Helicobacter pylori immunoglobulin G (IgG) antibodies may serve as an alternative diagnostic approach. This study aimed to determine the serological profile of anti-Helicobacter pylori IgG antibodies among patients with chronic gastritis attending the Baregbeg Community Health Center. A descriptive study was conducted involving 24 outpatients diagnosed with chronic gastritis who met the inclusion criteria. Participants were recruited using a total sampling technique. Serum samples were collected and analyzed using an immunochromatographic assay at the Baregbeg Community Health Center Laboratory between April and June 2025. All 24 participants (100%) tested negative for anti-Helicobacter pylori IgG antibodies. No serological evidence of Helicobacter pylori infection was detected among the study participants. In conclusion, no serological evidence of Helicobacter pylori infection was detected among chronic gastritis patients included in this study, with an observed Helicobacter pylori seropositivity rate of 0%.